A rare case of Bacillus megaterium soft tissues infection - Bocchi, Maria Beatrice; Cianni, Luigi; Perna, Andrea; Raffaele, Vitiello; Greco, Tommaso; Maccauro, Giulio; Perisano, Carlo (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: To report the history and clinical presentation of a 60-year-old male who developed a rare soft tissue infection of the right leg caused by Bacillus megaterium and to perform a Literature review focusing on clinical manifestations and diagnostic difficulties of the aforementioned bacterium. Methods: Medical history and clinical presentation suggested the infectious etiology, which led to the surgical procedure of fistulectomy and to further histological and microbiological investigations with bacterial cultures. Results: The histological report tested negative for osteomyelitis. Bacterial cultures revealed Bacillus megaterium, which was sensitive to all antibiotics against which it was tested. The oral antibiotic therapy was set for 12 days with benefits. The patient has always been apyretic, inflammation indexes and white cells count have been within normal limits. Conclusions: This was a rare case of soft tissue infection caused by Bacillus megaterium known to be a “non-pathogenic” bacterium. The infection was likely acquired by the penetration through the injury wound. The combination of surgical and antibiotic therapy lead to complete skin healing and infection resolution at the 6-months follow up.